Nonlinear Double-arm Optical Tweezers for Controlling 3D Microspheres - Thang, Nguyen Manh (Communications in Physics, 2020)
In this paper, a new nonlinear double-arm optical tweezer combining Mach-Zenhder interferometer, objective lens and organic dye layer is proposed. Based on the ray-optical and wave optical approximations, the expression describing the separation of two trap centers and laser intensity distribution is derived. The obtained results show that the separation between two trap centers, the laser intensity distribution, trap region's area and optical trap efficiency can be controlled by tuning laser power. The proposed model is seen to be a double-arm optical tweezer for controlling 3D microsphere by optical method.